1996
DOI: 10.1074/jbc.271.35.21579
|View full text |Cite
|
Sign up to set email alerts
|

The Amino-terminal Charge and Core Region Hydrophobicity Interdependently Contribute to the Function of Signal Sequences

Abstract: We have constructed a series of signal sequence mutants that contain negatively charged amino termini and simplified core regions of varying hydrophobicity levels. This series provides a means of exploring the relative roles of the amino terminus and the hydrophobic core region during transport. The signal peptides with highly hydrophobic core regions support a rapid rate of transport in the presence of a negatively charged amino terminus. We have found that these negatively charged mutants are secreted in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
1
34
3
Order By: Relevance
“…Although the Bla targeting pathway(s) has never been clearly identified, previous studies have shown that a variety of physiological insults that increase the presence of abnormal proteins (and that likely induce the heat shock response) lead to Bla export defects (7,34). These and other results (5) suggest that Bla is targeted by one or more heat shock-regulated chaperones such as DnaK or GroEL.…”
Section: Disruption Of Tig Reduces the Requirement For Targeting Factmentioning
confidence: 75%
“…Although the Bla targeting pathway(s) has never been clearly identified, previous studies have shown that a variety of physiological insults that increase the presence of abnormal proteins (and that likely induce the heat shock response) lead to Bla export defects (7,34). These and other results (5) suggest that Bla is targeted by one or more heat shock-regulated chaperones such as DnaK or GroEL.…”
Section: Disruption Of Tig Reduces the Requirement For Targeting Factmentioning
confidence: 75%
“…These charges within the sequence of the CCK-A receptor therefore promote membrane insertion, whereas the charges in the N-terminal region of the ␣ chain of the H,K-ATPase present in the HK-M0 vector do not. This result suggests that the positively charged cytoplasmic anchor and the hydrophobic sequence may also have to be in proximity to affect membrane insertion or orientation (35). Furthermore, when the H6 putative transmembrane domain is extended on the C-terminal side, including two positive and one negative charge (HK-M0/CCK6LC), this sequence also promotes a strong glycosylation of the ␤ region, therefore acting as a signal anchor.…”
Section: Discussionmentioning
confidence: 96%
“…2A). Earlier studies have demonstrated a clear correlation between the hydrophobicity of these signal peptides, the efficiency of in vivo transport (7,15), and cross-linking with P48 and with SecA (28) in vitro and with binding to SecA in reconstituted systems (21,29). secB ϩ and secB null cells transformed with the mutant alkaline phosphatases under the control of the lac promoter were pulse labeled with […”
mentioning
confidence: 99%